Epitranscriptomic control of telomere maintenance - Pashay Ahi, Ehsan; Ghasemishahrestani, Zeinab (Springer Nature, 2026)
Telomere maintenance has been portrayed primarily as a problem of DNA–protein architecture and chromatin control, yet a complementary layer has been revealed at the level of RNA chemistry. In this Review, RNA modifications and their writer–reader–eraser and RNA-editing systems are integrated into a framework for chromosome-end homeostasis. Epitranscriptomic regulation of the telomerase ribonucleoprotein is examined, and assembly, activity, and recruitment are shown to be reshaped by chemical marks on TERC, specialized RNA capping, and processing pathways. Telomeric transcripts, particularly TERRA, are discussed as modified substrates whose stability, trafficking, and propensity for telomeric RNA: DNA hybrid formation can be tuned by RNA marks and their readers. Downstream consequences for replication stress, DNA damage signaling, and recombination-driven alternative lengthening of telomeres are summarized, together with emerging examples in which modification of telomere-factor mRNAs has been linked to rewiring of maintenance networks. Across these themes, links to telomeropathies, aging-associated inflammation, environmental stressors, and cancer are collated to connect mechanism to phenotype. Experimental bottlenecks and opportunities—site-resolved mapping, locus-targeted editing, and pharmacologic modulation of RNA-modifying enzymes—are outlined as routes toward causal models and therapeutic utilization.